2022
DOI: 10.1038/s41598-022-14534-x
|View full text |Cite
|
Sign up to set email alerts
|

Horticulture therapy affected the mental status, sleep quality, and salivary markers of mucosal immunity in an elderly population

Abstract: Horticultural therapy (HT) has been reported to be beneficial to mental and physical health. This study investigated the effects of HT on the psychological status and mucosal immunity of elderly individuals. Twenty-four participants aged 70–93 were recruited from residential facilities and adult day-care services. Six different HT activities were designed and guided by licensed instructors who performed saliva collection and helped the participants complete the questionnaires before and after each activity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
5
0
2
Order By: Relevance
“…In order to highlight the distribution of relevant findings, the categories of horticultural therapy encounters were framed in terms of "accessibility," "engagement," and "exposure" to urban farming. Most of the effects on the horticultural therapy with urban farming elements (happiness, recovery, resilient, solidarity, responsible, positivity, optimism, harmonious, integration, satisfaction, confidence, enjoyment, relationships, healthy, and knowledgeable) were associated with more than one (1) horticultural therapy interaction, verifying the subject's therapeutic value as mentioned in earlier studies (Shen et al, 2022;Spano et al, 2020). Furthermore, among all, happiness and recovery effects were reported associated with engagement with horticultural therapy interaction only (Ambrose et al, 2020;Chan et al, 2015).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In order to highlight the distribution of relevant findings, the categories of horticultural therapy encounters were framed in terms of "accessibility," "engagement," and "exposure" to urban farming. Most of the effects on the horticultural therapy with urban farming elements (happiness, recovery, resilient, solidarity, responsible, positivity, optimism, harmonious, integration, satisfaction, confidence, enjoyment, relationships, healthy, and knowledgeable) were associated with more than one (1) horticultural therapy interaction, verifying the subject's therapeutic value as mentioned in earlier studies (Shen et al, 2022;Spano et al, 2020). Furthermore, among all, happiness and recovery effects were reported associated with engagement with horticultural therapy interaction only (Ambrose et al, 2020;Chan et al, 2015).…”
Section: Resultssupporting
confidence: 80%
“…This was explained by saying that horticultural therapy is a series of procedures intended to produce "preventive medical benefits" through exposure to natural stimuli that induce physiological relaxation and strengthen compromised immune systems to prevent disease (Lu et al, 2020;Van den Berg & Custers, https://doi.org/10.24191/bej.v21i1.401 ©Authors, 2024 2011). Horticultural therapy, in contrast to the "specific effects" predicted from pharmaceutical therapies, aims to boost immunity, prevent illnesses, preserve health, and promote health by exposing patients to nature and, as a result, promoting relaxation (Lu et al, 2020;Shen et al, 2022). Future urbanisation was anticipated to be further encouraged, and horticultural therapy was seen as useful in reducing the stress that urbanisation causes.…”
Section: Urban Farming Practices and Horticultural Therapymentioning
confidence: 99%
“…Studies have furthermore demonstrated the impact of horticultural therapy on reducing high blood pressure, heart rate and salivary cortisol levels in children and elderly people with mental health problems [33][34][35][36] . The impact of horticultural therapy on sleep 34 , depression 27 , mood enhancement 37 , improving physical capabilities 35 , stress 29,30,35 and improving quality of life 30 has already been evaluated. The results are significant, confirming that therapeutic gardening and gardening activities have a positive impact on overall human health.…”
Section: Discussionmentioning
confidence: 99%
“…Our trial did not take into account biological measures such as biomarkers, cortisol measurement and blood pressure measurement, which may prove to be a limitation. However, as mentioned above, other studies have shown convincing results of horticultural therapy on biological markers [33][34][35][36] and we have chosen to focus on anxiety to contribute to our knowledge base.…”
Section: Limitationsmentioning
confidence: 99%
“…The salivary α-amylase activity was determined using a kinetic reaction assay kit (Salimetrics LLC., State College, PA, USA). Both methods were used by following the manufacturer's instructions [41,42]. The concentrations of salivary lactoferrin, IgA, testosterone, and cortisol were measured using enzyme-linked immunosorbent assays (ELISA, Calbiochem, Darmstadt, Germany) following the manufacturer's instructions.…”
Section: Analysis Of Salivary Proteinsmentioning
confidence: 99%